Motivating Knowledge Worker Using Financial Rewards - Ren, Siqi (2017)
Nowadays, the competitions among organizations is not only limited to the technology area and the management area, but also to the talent area. Furthermore, knowledge workers are one of the most important assets of an organization. They are major role-players in creating profit. Thus, we need to understand how to take advantage of this type of human resource and therefore how to motivate knowledge workers in the organization becomes a point of issue. Resolving this problem entails building an effective knowledge workers motivation system. And the most sensitive part of this system is that of compensation incentives.